Flat soliton microcomb source - Wang, Xinyu; Qiu, Xuke; Liu, Mulong; Liu, Feng; Li, Mengmeng; Xue, Linpei; Chen, Bohan; Zhang, Mingran; Xie, Peng (Opto-Electronic Science, 2023)
Mode-locked microcombs with flat spectral profiles provide the high signal-to-noise ratio and are in high demand for wavelength division multiplexing(WDM)-based applications,particularly in future high-capacity communication and paral-lel optical computing.Here,we present two solutions to generate local relatively flat spectral profiles.One microcavity with ultra-flat integrated dispersion is pumped to generate one relatively flat single soliton source spanning over 150 nm.Besides,one extraordinary soliton crystal with single vacancy demonstrates the local relatively flat microcomb lines when the inner soliton spacings are slightly irregular.Our work paves a new way for soliton-based applications owing to the rel-atively flat spectral characteristics.